Biomimetic strategies for the deputization of proteoglycan functions - Rehan, Ibrahim F.; Elnagar, Asmaa; Zigo, František; Sayed-Ahmed, Ahmed; Yamada, Shuhei (Frontiers in Cell and Developmental Biology, 2024)
Proteoglycans (PGs), which have glycosaminoglycan chains attached to their protein cores, are essential for maintaining the morphology and function of healthy body tissues. Extracellular PGs perform various functions, classified into the following four categories: i) the modulation of tissue mechanical properties; ii) the regulation and protection of the extracellular matrix; iii) protein sequestration; and iv) the regulation of cell signaling. The depletion of PGs may significantly impair tissue function, encompassing compromised mechanical characteristics and unregulated inflammatory responses. Since PGs play critical roles in the function of healthy tissues and their synthesis is complex, the development of PG mimetic molecules that recapitulate PG functions for tissue engineering and therapeutic applications has attracted the interest of researchers for more than 20 years. These approaches have ranged from semisynthetic graft copolymers to recombinant PG domains produced by cells that have undergone genetic modifications. This review discusses some essential extracellular PG functions and approaches to mimicking these functions.